Does Daily Moderate-to-Vigorous Physical Activity Affect Glycemic Control Equally Across Populations? Insights From NHANES 2005–2006 - Z. Helen Wu; Yunqi Wang; Taiwo F. Ajibola; Helen Swede; Emil Coman; Gualberto Ruano; James J Grady (American Journal of Lifestyle Medicine, 2026)
Current physical activity (PA) guidelines for chronic disease management (e.g., diabetes) are based on population averages and may not reflect physiological differences across racial/ethnic groups. This study investigates whether the association between PA and glycemic control varies among Non-Hispanic White (NHW), Non-Hispanic Black (NHB), and Mexican American (MA) adults. We analyzed weighted NHANES 2005-2006 data in adults aged ≥20 (n = 2354 unweighted). PA was measured via accelerometer (≥10 hours/day, 4-7 days) and glycemic control was assessed using HbA1c, categorized as normal (